Directed swarm assembly due to mixed misaligned perception-dependent motility - Rodrigo Saavedra; Marisol Ripoll (Communications Physics)
Abstract Biological entities as diverse as birds or bacteria frequently self-assemble to display sophisticated collective dynamical behaviors. To understand and design interactions between the individual entities that originate the different flocking behaviors is one of the current most significant challenges in active matter. Here we show how a mixture of particles with perception-dependent motility and opposite misaligned visual perception spontaneously organizes into a self-propelling bean-shaped cluster. The two species initially rotate in opposite directions which, together with the steric interactions, make them segregate into two main counter-rotating domains forming a cohesive and persistently propelling single cluster. Mixtures of particles with misaligned perception and discontinuous motility are therefore a promising pathway for the design of programmable active matter.